The U Visa for Immigrant Victims of Violent Crime: What Social Workers Need to Know. Issue 4 (1st October 2016) - Warren, Sherry
ABSTRACT: Immigrant victims of violent crime can obtain citizenship in the United States through the U Visa provision of the Violence Against Women Act of 2000. Social workers must engage with community agencies and law enforcement to increase awareness of the U Visa, streamline the process, and convince legislators to undertake revisions that address current gaps and increase community safety.